A Beam-Scanning Array Antenna for LPWAN Base Station - Ngamjanvaporn, Phaisan; Phongcharoenpanich, Chuwong; Krairiksh, Monai (My University, 2018)
This paper presents a beam-scanning array antenna for LPWAN base station. The two-element array of the pattern reconfigurable Yagi-Uda antennas is designed at the 2.4 GHz ISM band to provide 360° beam-scanning. The characteristics of the array are simulated using the 4NEC2 simulator. By using the pattern reconfigurable elements and with non-uniform amplitude excitation, the simulated results show that the array provides 16 beams covering 360° with 7 dBi gain. Also, the S 11 bandwidth of the array is satisfied to the desired operating frequency.
Keywords: Beam-scanning array antenna; LPWAN; Yagi-Uda antenna